Ngaben Conception In Lontar Siwa Tattwa Purana - I Nyoman Kiriana (Institut Hindu Dharma Negeri Denpasar, 2017)
Generally, in most traditions every birth and death will be made a ritual. The implementation of these rituals will usually be adapted to the local culture. Thus in the implementation order will vary, but the substance is the same. In the tradition of the Hindu community in Bali, if there are people who died will be made Ngaben ceremony, as a form of respectful and responsibility. In the implementation of this Ngaben ceremony will always be guided by the sacred books and will be adapted to the local tradition. One of the sacred books guided in Ngaben’s ceremony is Lontar Siva Tattwa Purana. In this Lontar explained that Ngaben ceremony is an obligation of his descendants as one of the payment of Rna (debt) to his ancestors. In practice it, must be adjusted to the level of ability of his or her generation for all harmony. Further , will be explained the procedure of Ngaben ceremony in this Lontar start from the beginning to the end.